2023
DOI: 10.1371/journal.pone.0284928
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and associated factors for self-reported symptoms of dry eye among Thai school children during the COVID-19 outbreak

Abstract: Purpose COVID-19 pandemic caused an increase in digital screen time, which seemed to increase the prevalence of dry eye symptoms among the population with abnormally high digital screen usage hours. However, there are no reports of dry eye symptoms in school children with high digital usage hours. Therefore, the present study aimed to assess the prevalence of dry eye symptoms and evaluate the associated factors among school children aged 12 to 18 years during the COVID-19 outbreak. Methods Multistage cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Dry Eye: Dry eye disease was reported in high rates among subjects affected by COVID-19 disease. School-based research revealed a preponderance of dry eye as measured with a validated paper-based instrument [ 43 ]. Female gender and being of an older age were indicated as exacerbating risk factors [ 44 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…Dry Eye: Dry eye disease was reported in high rates among subjects affected by COVID-19 disease. School-based research revealed a preponderance of dry eye as measured with a validated paper-based instrument [ 43 ]. Female gender and being of an older age were indicated as exacerbating risk factors [ 44 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%